Second Primary Lung Cancer After Breast Cancer: A Population-Based Study of 6,269 Women - Wang, Rong; Yin, Zhiqiang; Liu, Lingxiang; Gao, Wen; Li, Wei; Shu, Yongqian; Xu, Jiali (Frontiers in Oncology, 2018)
Purpose: Breast cancer (BC) and lung cancer are the most two common cancers with highest morbidity and mortality for women. With prolonged survival, there comes the possibility that BC patients will develop second primary cancers. We evaluate the characteristics, incidence and survival of second primary non-small cell lung cancer (BC-NSCLC) and small cell lung cancer (BC-SCLC) after breast cancer. Patients and methods: Second primary lung cancer risks using standardized incidence ratios (SIRs) [95% confidence intervals (95% CIs)] were calculated among breast cancer patients in SEER-18 (2000–2014). Survival outcomes were also analyzed for both BC-NSCLC and BC-SCLC. Results: A total of 6,269 second lung cancer patients after a localized or regional BC were identified. The incidence rate was modestly higher compared to the general population (SIR = 1.03; 95%CI: 1.00–1.06). For ER-, PR- and HER2- groups, SIRs were 1.26, 1.16, 1.13, respectively (all p < 0.05). Triple negative breast cancer (TNBC) patients have an even higher incidence rate of lung cancer (SIR = 1.59, 95%CI: 1.29–1.94). Elevated SIRs were also observed among the following groups: within 1 year after BC diagnosed, a young age at BC diagnosed, black people, poorly or undifferentiated histological grade of breast cancer. Median survival (MST) after localized, regional and distant BC-NSCLC was 68.0, 26.0, and 6.0m. Five-year survival rates for BC-NSCLC were 53.9, 29.8 and 5.7% in each stage, which were significantly higher compared to first primary NSCLC (all p < 0.001). ER-/PR- or TNBC were unfavorable prognostic factors for BC-NSCLC. The survival rates of BC-SCLC were no significant different compared to first primary SCLC. Conclusion: BC patients, especially for TNBC, are at a high risk of developing second primary lung cancers. BC history may be a favorable prognostic factor for NSCLC (but not SCLC) patients. Clinicians should closely follow up BC patients with high-risk factors.